Mutational Dynamics of Aroid Chloroplast Genomes II - Abdullah; Henriquez, Claudia L.; Croat, Thomas B.; Poczai, Peter; Ahmed, Ibrar (Frontiers in Genetics, 2021)
The co-occurrence among single nucleotide polymorphisms (SNPs), insertions-deletions (InDels), and oligonucleotide repeats has been reported in prokaryote, eukaryote, and chloroplast genomes. Previously, correlations among SNPs, InDels, and repeats were investigated in the plant family Araceae using pair-wise sequence alignments of the chloroplast genomes of two morphotypes of one species, Colocasia esculenta belonging to subfamily Aroideae (crown group), and four species from the subfamily Lemnoideae, a basal group. The family Araceae is a large family comprising of 3645 species in 144 genera, grouped in eight subfamilies. In the current study, we performed 34 additional comparisons using 27 species from 7 subfamilies of Araceae to determine correlation coefficients among the mutational events at the family, subfamily, and genus levels. We express strength of the correlations as: negligible or very weak (0.1–0.19), weak (0.20–0.29), moderate (0.30–0.39), strong (0.4–0.69), very strong (0.70–0.99), and perfect (1.0). We observed strong/very strong correlations in most comparisons, whereas a few comparisons showed moderate correlations. The average correlation coefficient was recorded as 0.66 between “SNPs and InDels”, 0.50 between “InDels and repeats” and 0.42 between “SNPs and repeats”. In qualitative analyses,95%–100% of the repeats at family and sub-family level, while 36%–86% of the repeats at genus level comparisons co-occurred with SNPs in same bins. Our findings show that such correlations among mutational events exist throughout the family Araceae and support the hypothesis of distribution of oligonucleotide repeats as a proxy for mutational hotspots.